Temperature effects on the ionic conductivity in concentrated alkaline electrolyte solutions. Issue 19 (2nd January 2020) - Shao, Yunqi; Hellström, Matti; Yllö, Are; Mindemark, Jonas; Hermansson, Kersti; Behler, Jörg; Zhang, Chao
Abstract : Reactive molecular dynamics simulations show how ion-paring, cross-correlated ion motions and proton transfer contribute to the ionic conductivity in concentrated NaOH solutions at elevated temperatures. Abstract : Alkaline electrolyte solutions are important components in rechargeable batteries and alkaline fuel cells. As the ionic conductivity is thought to be a limiting factor in the performance of these devices, which are often operated at elevated temperatures, its temperature dependence is of significant interest. Here we use NaOH as a prototypical example of alkaline electrolytes, and for this system we have carried out reactive molecular dynamics simulations with an experimentally verified high-dimensional neural network potential derived from density-functional theory calculations. It is found that in concentrated NaOH solutions elevated temperatures enhance both the contributions of proton transfer to the ionic conductivity and deviations from the Nernst–Einstein relation. These findings are expected to be of practical relevance for electrochemical devices based on alkaline electrolyte solutions.